Parâmetros fisiológicos do feijão de corda submetido à salinidade em diferentes estádios de desenvolvimento. - Calvet, Amanda Soraya Freitas (2009)
The objective of this study the effects of water (CEw = 0.5 dS m-1) and saline solution (CEw = 5.0 dS m-1) applications, alternately, at different stages of development of cowpea cv. Epace 10. Two experiments were conducted under conditions of greenhouse in Embrapa Agroindústria Tropical. In both, seeds were placed into pots arranged in a randomized block design with six treatments and four replications. In the first experiment the plants irrigated with water or saline solution were collected at different times of development: 12, 42 and 55 days after sowing. CEes, as Cl-, Na + and K + in the soil, parameters of plant growth (dry weight of plant parts, leaf area, height and number of leaves), water potential and osmotic and inorganic solutes were evalueted. In the second experiment, water and saline solution were applied during the following stages of plant development: PHASE I - from germination to the appearance of the first trifoliolate leaf .PHASE II - the appearance of the first trifoliolate leaf until the beginning of flowering; PHASE III - flowering until the complete formation of the first pods, producing the following treatments: 1. irrigation with water until the end of phase III, 2. irrigation with saline solution until the end of Phase III, 3. water until the end of phase I and saline solution until the end of Phase III, 4. Saline solution until the end of phase I and water until the end of Phase III, 5.irrigation with water until the end of phase II and saline solution until the end of Phase III, 6.irrigation with saline solution until the end of phase II and water until the end of phase III. The parameters gas exchange and inorganic solutes were evaluated too. Flowering and fruiting stages were the most affected by salinity. The photosynthetic rate was not affected by salinity in plants shoots, especially leaves, when applied in more than one phase of growth, regardless of the stage where the stress began in both experiments. In leaves, the soluble carbohydrates were not affected by salt stress, while the amino acids increased when salt was applied throughout the experimental period. In roots, organs that were in direct contact with the salt decreased the levels of both proteins and amino acids. The transport of Na+ was restricted to the leaf with the same accumulated on the stem, while for the Cl- plants had a typical response of glycophyte with the highest level of this ion in the leaves. The cowpea irrigation with saline solution is possible, provided it is applied to only part of the cycle of crop growth, alternating with the application of water of superior quality.